# |
ODE |
Mathematica |
Maple |
\[
{}\sin \left (x \right )^{2} y^{\prime \prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x \right ) y^{\prime \prime }+\left (4 x +2\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{x} = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }-\cos \left (x \right ) y^{\prime }+2 y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-6 x = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }-5 x^{\prime }-3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2}+x^{\prime }+\frac {x}{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2}+x^{\prime }+\frac {x}{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+6 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-12 x = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }+3 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2}+\frac {5 x^{\prime }}{6}+\frac {2 x}{9} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {x^{\prime }}{8}+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = -\frac {x}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = \frac {4 x}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+3 t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+4 x^{\prime }+\frac {2 x}{t} = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-7 t x^{\prime }+16 x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+3 t x^{\prime }-8 x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+t x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-t x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+t^{2} x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-t x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 a x^{\prime }+a^{2} x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-\frac {\left (2+t \right ) x^{\prime }}{t}+\frac {\left (2+t \right ) x}{t^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+t x^{\prime }+\left (t^{2}-\frac {1}{4}\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime }-6 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime }-3 \left (1+x \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x +1\right ) y^{\prime \prime }-\left (x^{2}+x \right ) y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right ) y^{\prime \prime }-4 \left (1+x \right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}-x^{2}\right ) y^{\prime \prime }-\left (x^{3}+2 x^{2}-2 x \right ) y^{\prime }+\left (2 x^{2}+2 x -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-12 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }-14 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }+4 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-6 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+29 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+58 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+6 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+37 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }-4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }-10 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +2\right )^{2} y^{\prime \prime }-\left (x +2\right ) y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|